Brain Storm The Flaws in the Science of Sex Differences - Jordan-Young, Rebecca M. 1963- (Harvard University Press, 2021)
Jordan-Young has written a stunning book that demolishes most of the science associated with the dominant paradigm of the development of sex and gender identity, behavior, and orientation. The current paradigm, brain organization theory, proposes: "Because of early exposure to different sex hormones, males and females have different brains"; and these hormones also create "gay" and "straight" brains. Jordan-Young interviewed virtually every major researcher in the field and reviewed hundreds of published scientific papers. Her conclusion: "Brain organization theory is little more than an elaboration of longstanding folk tales about antagonistic male and female essences and how they connect to antagonistic male and female natures." She explains, in exquisite detail, the flaws in the underlying science, from experimental designs that make no statistical sense to "conceptually sloppy" definitions of male and female sexuality, contradictory results, and the social construction of normality. Her conclusion that the patterns we see are far more complicated than previously believed and due to a wider range of variables will shake up the research community and alter public perception
Description based on online resource; title from PDF title page (publisher's Web site, viewed 21. Jun 2021)
Keywords: SCIENCE / Life Sciences / Developmental Biology; Brain -- Sex differences; Sex differeances -- Research; Gehirn; Geschlechtsunterschied